A 3-D constitutive model for pressure-dependent phase transformation of porous shape memory alloys. (February 2015) - Ashrafi, M.J.; Arghavani, J.; Naghdabadi, R.; Sohrabpour, S.
Abstract: Porous shape memory alloys (SMAs) exhibit the interesting characteristics of porous metals together with shape memory effect and pseudo-elasticity of SMAs that make them appropriate for biomedical applications. In this paper, a 3-D phenomenological constitutive model for the pseudo-elastic behavior and shape memory effect of porous SMAs is developed within the framework of irreversible thermodynamics. Comparing to micromechanical and computational models, the proposed model is computationally cost effective and predicts the behavior of porous SMAs under proportional and non-proportional multiaxial loadings. Considering the pressure dependency of phase transformation in porous SMAs, proper internal variables, free energy and limit functions are introduced. With the aim of numerical implementation, time discretization and solution algorithm for the proposed model are also presented. Due to lack of enough experimental data on multiaxial loadings of porous SMAs, we employ a computational simulation method (CSM) together with available experimental data to validate the proposed constitutive model. The method is based on a 3-D finite element model of a representative volume element (RVE) with random pores pattern. Good agreement between the numerical predictions of the model and CSM results is observed for elastic and phase transformation behaviors in various thermomechanical loadings. Abstract : Highlights: A model is proposed for pseudo-elastic behavior and shape memory effect of porous SMAs. Pressure dependent phase transformation of porous SMAs is investigated. A computational simulation method is utilized for validation under general loadings. The model predicts behavior under proportional and non-proportional loadings. Shear–volumetric coupling of responses is observed under non-proportional loading.